(untitled) (Research, Society and Development, 2022)
Assessing water quality makes it possible to develop decision-making strategies related to water use. The Jaime Umbelino de Souza dam was built to regulate the flow of the Poxim-Açu River and supply the metropolitan region of Aracaju, Sergipe. Therefore, the main objective of this work was to evaluate the physicochemical characteristics of the water from the Jaime Umbelino de Souza dam, and for that, two campaigns were carried out, where the collection points were defined so that they represented the aspects of the dam water. The parameters dissolved oxygen (DO), temperature, turbidity, total phosphorus, total dissolved solids, and nitrate were analysed. The index proposed by CETESB (WQICETESB) and the weighted arithmetic water quality index (WQIAP) were used to evaluate the water quality. All analysed parameters did not exceed the limits set by the CONAMA resolution number 357. After statistical selection, water temperature, total phosphorus and the ions magnesium, nitrate, chloride, sodium, and calcium were the variables that most influenced the water quality. The application of index to assess water quality indicated “Good” and “Excellent” quality for WQICETESB and WQIAP, respectively, with no sign of degraded sites. The continuous environmental monitoring of the area is recommended, along with the inclusion of new variables, new sampling campaigns for investigating seasonal factors, management, and integration with environmental policies.